Potensi CtpF pada Mycobacterium tuberculosis dalam Pengembangan CtpF-Inhibitor sebagai Inovasi Terapi Target Mutakhir pada Pengobatan TB MDR/XDR - Rahmatika, Alfi; Mufaiduddin, Muhammad; Innelya, Innelya (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2023)
Background: Tuberculosis (TB) is one of the major causes of death in the world with the number of cases reaching millions every year. TB is caused by Mycobacterium tuberculosis. The occurrence of mutations in M. tuberculosis that cause resistance to anti-tuberculosis drugs has become a health crisis in TB treatment. Drug resistance in TB consists of MDR TB and XDR TB. The incidence of MDR/XDR TB has increased rapidly in the world with total MDR TB cases reaching more than 480 thousand each year and 9% of those develop into XDR TB. Therefore, it is requisite to develop new therapeutic targets to reduce the prevalence of MDR/XDR TB. CtpF in M. Tuberculosis is the latest innovative therapeutic target in making a new anti-tuberculosis drug because it plays important role in M. tuberculosis homeostasis. Method: This study was made using a non-systematic review method with four sources of publication and several keywords. Overall, 88 pieces of literature that meet the inclusion criteria were used. Results and Discussion: CtpF is a type of P-type ATPase that transports Ca2+ ions and plays important role in responding to intraphagosomal stress conditions that are important for bacterial survival. Inhibition of CtpF can pull down Ca2+ homeostasis in M. tuberculosis so that it is unable to carry out various biomolecular processes and lose defense mechanisms against stress conditions. In addition, CtpF also has a very low mutation ability. This makes CtpF a druggable target for designing new anti-tuberculosis therapy that is not susceptible to resistance. Conclusion: CtpF-inhibitor candidates have the potential to be developed as the latest target therapy in the treatment of MDR / XDR TB.